Dihydropyridine-derived calcium channel blocker as a promising anti-hantavirus entry inhibitor - Wang, Bin; Pei, Jiawei; Zhang, Hui; Li, Jia; Dang, Yamei; Liu, He; Wang, Yuan; Zhang, Liang; Qi, Libin; Yang, Yuewu; Cheng, Linfeng; Dong, Yangchao; et al. (Frontiers in Pharmacology, 2022)
Hantaviruses, the causative agent for two types of hemorrhagic fevers, hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS), is distributed from Eurasia to America. HFRS and HPS have mortality rates of up to 15% or 45%, respectively. Currently, no certified therapeutic has been licensed to treat hantavirus infection. In this study, we discovered that benidipine hydrochloride, a calcium channel blocker, inhibits the entry of hantaviruses in vitro. Moreover, an array of calcium channel inhibitors, such as cilnidipine, felodipine, amlodipine, manidipine, nicardipine, and nisoldipine, exhibit similar antiviral properties. Using pseudotyped vesicular stomatitis viruses harboring the different hantavirus glycoproteins, we demonstrate that benidipine hydrochloride inhibits the infection by both HFRS and HPS-causing hantaviruses. The results of our study indicate the possibility of repurposing FDA-approved calcium channel blockers for the treatment of hantavirus infection, and they also indicate the need for further research in vivo.